Association Between Multidrug-Resistant Organisms (MDROs) And Mortality In Sepsis Patient At RSUP Dr. M. Djamil Padang - Ayuni, Alya Syafa; Fadrian, Fadrian (E-Jurnal Medika Udayana; Vol 13 No 11 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i11.P07, 2024)
Multidrug-resistant organisms (MDROs) is a condition where bacteria are resistant to at least 1 type of antibiotic from ?3 classes of antibiotics. Bacteria are one of the causes of infection. If the treatment of infection is not optimal, it can cause patients to experience a more severe condition, that is sepsis. Sepsis is the leading cause of death from infection. This study aimed to determine the association between Multidrug-Resistant Organisms (MDROs) and mortality in sepsis patients.This study is an analytical study with a cross-sectional design using secondary data sourced from medical record data of hospitalized sepsis patients in the internal medicine section of RSUP Dr. M. Djamil Padang in 2022. The sampling technique was total sampling. The number of samples that met the criteria was 99 samples. Data analysis used a chi-square test. The results of this study showed that sepsis patients were dominated by female (55.6%), aged ?60 years (55.6%), with the most common source of infection being the respiratory system (83.8%), and the use of the most used medical device was NGT (90.9%), the outcome of death in sepsis patients was 53 patients (53.5%). Multidrug-resistant organisms (MDROs) bacteria that cause the most sepsis patients are ESBL-producing Klebsiella pneumoniae as many as 29 isolates (39.2%) with the most specimen collection is sputum, which is 40 specimens (54.1%). Multidrug-resistant organisms (MDROs) bacteria in sepsis patients with the highest death outcome were ESBL-producing Escherichia coli with 16 isolates (21.6%). The results of the Chi-square test of multidrug-resistant organisms (MDROs) bacteria with sepsis patient mortality in this study obtained a value of p=0.743. This study concludes that there is no significant association between multidrug-resistant organisms (MDROs) and mortality in sepsis patient